(untitled) (Medical Forum Monthly, 2024)
Objectives: To see the frequency of ABO, subgroup ABO and Rh(D) blood groups in Patients, & donors, who attended the Liaquat university hospital for any type of surgery, Gynaecology & Obstratical problem, etc, of Hyderabad & its territory. Study Design: Cross- sectional study. Place and Period of Study: Department of Pathology and Diagnostic and Research Laboratory, LUMHS, Jamshoro/ Hyderabad, from February,2012 to March, 2012. Materials and Methods: Donors and patients of both sexes, blood samples were collected under aseptic condition from anti-cubital vein for determination of blood groups. subjects belonging to Hyderabad & its Territory, were included in this study. ABO blood grouping was determined by tile method using commercially prepared anti sera, anti A, anti B, anti AB (Plasmatic Kent, UK). Presence of Rh D antigen was determined by anti-D (Biotic Laboratories Ltd UK). For Rh-negative Du test was done. Results: Our study shows, A positive-22.88%, A negative-02.31%, B positive-33.85%, B negative -03.27%, AB positive-08.27%, AB negative-0.77%, O positive-26.73%, O negative -01.92%. Conclusion: regarding the management of blood bank and transfusion services in this area. ABO and Rh antigenic structure differs between regions and nations. Knowledge of blood group distribution may also play an important role for clinical studies, reliable geographical information and for forensic studies in the populations. Such studies need to be carried out at all the regional levels of Pakistan.